Corruption in Global Times. A Critical Look at Transnational Governance - Lascurain Fernández, Mauricio (2025)
Globalization has had a significant impact on corruption, both within and between countries. However, it remains unclear whether corruption has increased or decreased as a result of globalization. This chapter analyzes the relationship between globalization and corruption, identifying the factors that contribute to each. It also highlights gaps in current research, which need to be addressed to better understand this complex phenomenon. To this end, it is divided into three sections. First, the theoretical model of corruption is described as an interaction between enabling and disabling factors at the international level, beyond the typical unit of analysis of the nation-state. Second, an overview of empirical findings is provided on how globalization can offer new resources for corruption, as well as new constraints. Finally, this paper highlights state interest in enforcement practices to understand why corruption control is currently considered to be in a difficult position.